2021
DOI: 10.1080/23311975.2021.1939837
|View full text |Cite
|
Sign up to set email alerts
|

Egotism and female managerial performance in South Africa: Evidence from SMEs in the agricultural sector

Abstract: This study sets out to address the perceived pitfalls of egotism among female entrepreneurs in South Africa. This study further ascertains a unique strategy and group of accustomed performance factors that are believed to serve as a cognitive antidote for female entrepreneurs to consistently out-manoeuvre the dangers of egotism. This study adopted a qualitative approach in which 16 achieving female entrepreneurs were purposively selected. The primary data was collected through the application of professionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…are four Khan studies, which refer to the study of creativity and innovating ability, risk-taking tendencies, proactiveness, and autonomy. [3] Their study of sixteen women business owners in South Africa uses interpretative phenomenological analysis (IPA) methodology to get the facts behind an event separate from each other. Through this IPA, researchers can get closer to the object of the study to collect, translate, and analyze each individual's specific real-life [17] Factors that contribute to performance are mentioned, each having three indicators: psychological, personal, and business.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…are four Khan studies, which refer to the study of creativity and innovating ability, risk-taking tendencies, proactiveness, and autonomy. [3] Their study of sixteen women business owners in South Africa uses interpretative phenomenological analysis (IPA) methodology to get the facts behind an event separate from each other. Through this IPA, researchers can get closer to the object of the study to collect, translate, and analyze each individual's specific real-life [17] Factors that contribute to performance are mentioned, each having three indicators: psychological, personal, and business.…”
Section: Resultsmentioning
confidence: 99%
“…and E.O., as the mirrored dimensions are incomplete although widely cited in the literature, especially for E.O. [3], Explaining that the study has three main limitations faced quite commonly in interpretative phenomenological analysis (IPA) studies but does not negatively affect the overall findings and conclusions of the paper, namely: (1) relatively small sample size, (2) subjects under relatively new investigation for entrepreneurial research, limited access in obtaining supporting data through studies conducted, (3) this study discusses certain groups of performance factors that require researchers to remain within the context of the specified research. [5] His research revealed that his research had two main shortcomings, namely (1) data limitations using dichotomous variables and not considering additional dependent variables such as actual sales data and not measuring the extent of the effect of training on company performance between different companies.…”
Section: Weaknesses From Various Hrm Andmentioning
confidence: 99%
See 3 more Smart Citations